A study on management practices and manufacturing performance in India and Malaysia. Issue 3 (7th August 2017) - Sakikawa, Takashi; Chaudhuri, Kaushik; Arif, Nurhaizal Azam
Abstract : Purpose: The purpose of this study is to explore the relationship between management practices and manufacturing performance, based on evidence from India and Malaysia – two countries from the cultural area of Southern Asia. Design/methodology/approach: The authors theorized by drawing not only on the strategic human resource management (SHRM) literature but also on cross-cultural research. A total of 233 leaders constituted this study's sample: 96 production leaders from 16 Indian companies and 137 production leaders from 16 Malaysian companies participated in the survey. Findings: Some of the high-performance work practices (HPWPs) were effective across India and Malaysia. The use of HPWPs in Indian culture led to better manufacturing performance than the use of HPWPs in Malaysian culture. Research limitations/implications: This study did not measure national culture itself but instead used a dummy-coded variable of country as its proxy. Not only can national culture explain varieties in management practices including HPWPs, but it can also interact with these practices to affect performance. Practical implications: Indian and Malaysian managers can learn about their management practices from this, and they can learn about benefits they might bring to their workplaces if they manage through the use of HPWPs. Originality/value: The authors' research provides insight into the capability of national culture to moderate the relationship between HPWPs and manufacturing performance, even among two countries situated in the same region of Southern Asia.